Prevalence and associated factors of maternal depression among mothers of children with undernutrition at comprehensive specialized hospitals in Northwest Ethiopia in 2023: a cross−sectional study - Yenealem, Biazin; Negash, Misrak; Madoro, Derebe; Molla, Alemayehu; Nenko, Goshu; Nakie, Girum; Getnet, Berhanie (Frontiers in Psychiatry, 2024)
Background: Malnutrition is one of the most significant child health problems in developing countries, accounting for an estimated 53% of child deaths per year. Depression is the leading cause of disease-related disability in women and adversely affects the health and well-being of mothers and their children. Studies have shown that maternal depression has an impact on infant growth and nutritional status. However, evidence is scarce regarding the relationship between maternal depression and child malnutrition.The general objective of this study was to assess the prevalence and associated factors of maternal depression among mothers of undernourished children at Comprehensive Specialized Hospitals in Northwest Ethiopia, 2023.Methods: An institution-based cross-sectional study was conducted among 465 participants.Outcome variables were assessed using a Patient Health Questionnaire (PHQ-9). Data were analysed using SPSS-25. Bivariate and multivariable logistic regression analyses were conducted. Variables with a p-value less than 0.05 were considered statistically significant with corresponding 95% CI.The prevalence of maternal depression among mothers of children with undernutrition was 36.4% (95% CI: 32-41%). According to a multivariate analysis, lack of maternal education (AOR = 2.872, 95% CI = 1.502-5.492), unemployment (AOR =2.581, 95% CI = 1.497-4.451), poor social support (AOR =2.209, 95%CI = 1.314-3.713), perceived stigma (AOR = 2.243, 95% CI = 1.414-3.560), and stunting (AOR = 1.913, 95% CI = 1.129-3.241) were factors significantly associated with maternal depression.The overall prevalence of maternal depression was higher among mothers of children with undernutrition. This higher prevalence was associated with several factors, including lack of education, unemployment, poor social support, high perceived stigma, and stunted physical growth in the children themselves. To decrease maternal depression, we can address these factors by increasing the level of maternal education and employment opportunities, strengthening social support systems, reducing stigma, and providing interventions to reduce stunting.